Olfactometer Responses of Convergent Lady Beetles Hippodamia convergens (Coleoptera: Coccinellidae) to Odor Cues from Aphid-Infested Cotton Plants Treated with Plant-Associated Fungi - Janaina Camara Siqueira da Cunha; Morgan H. Swoboda; Gregory A. Sword (Insects, 2022)
Microbes have the potential to affect multitrophic plant–insect–predator interactions. We examined whether cotton plants treated with potentially beneficial fungi affect interactions between cotton aphids Aphis gossypii and predatory lady beetles Hippodamia convergens. We used Y-tube olfactometer assays to test lady beetle behavioral responses to stimuli emitted by aphid-infested and non-infested cotton plants grown from seeds treated with either Phialemonium inflatum (TAMU490) or Chaetomium globosum (TAMU520) versus untreated control plants. We tested a total of 960 lady beetles (480 males and 480 females) that had been deprived of food for approximately 24 h. In the absence of any fungal treatments, males preferred stimuli from aphid-infested plants, and females spent more time associated with stimuli from aphid-infested versus non-infested plants. When fungal treatments were added, we observed that lady beetles preferred non-aphid-infested P. inflatum plants, and males responded slower to plants treated with P. inflatum in the absence of aphids. We found some evidence to suggest that lady beetle behavioral responses to plants might vary according to the fungal treatment but not strongly impact their use as part of an insect pest management strategy.